Level Penalaran Kognitf Siswa pada Materi Kedatangan Bangsa-Bangsa Barat ke Indonesia Kelas VIII SMPN 7 Toli-Toli - Masriani Masriani (Universitas Tadulako, 2022)
This study aims to determine the cognitive reasoning level of students on the material of the arrival of western nations to Indonesia. This research includes quantitative descriptive research. This study involved 30 students of class VIII SMPN 7 Toli-Toli. Data collection techniques in this study was through the provision of tests. The instrument used consisted of 10 diagnostic items in the form of four tiers. The results showed that in the pattern of cognitive reasoning for the formal category was 3.3%, transitional was 67.7%, and concrete was 20.0%. Based on the cognitive level of students' cognitive reasoning level, the results obtained were evaluating 20.0%, analyzing 33.3%, and applying 46.7%. Based on the results, it is known that the highest level of cognitive reasoning possessed by students is applying and the lowest is evaluating.